"Time and Tide" : the feminist and cultural politics of a modern magazine - Clay, Catherine, 1971- (Edinburgh : Edinburgh University Press Ltd, 2018)
"The first in-depth study of the landmark modern feminist magazine, "Time and Tide." Unique in establishing itself as the only female-run intellectual weekly in the golden age of the weekly review, "Time and Tide" both challenged persistent prejudices against women's participation in public life and played an instrumental role in redefining women's gender roles and identities. Drawing on extensive new archival research, Catherine Clay recovers the contributions to this magazine of both well- and lesser-known British women writers, editors, critics and journalists and explores a cultural dialogue about literature, politics and the arts that took place beyond the parameters of modernist 'little magazines.' The book makes a major contribution to the history of women's writing and feminism in Britain between the wars."--Publisher's description
Introduction : "Time and Tide" origins, founders, and goals -- Part I. The early years, 1920-1928 ; A new feminist venture : work, professionalism and the modern woman -- 'The Weekly Crowd. By Chimaera' : collective identities and radical culture -- Mediating culture : modernism, the arts and the woman reader -- Part II. Expansion, 1928-1935 ; 'The Courage to Advertise' : cultural tastemakers and 'journals of opinion' -- 'A Common Platform' : male contributors and cross-gender collaboration -- 'The Enjoyment of Literature' : women writers and the 'battle of the brows' -- Part III. Reorientation, 1935-1939 ; A new partnership : art, money and religion -- A 'free pen' : women intellectuals and the public sphere -- Coda.
Includes bibliographical references (pages 279-295), and index.
Print version record.
eBooks on EBSCOhost
Keywords: Time and tide; Time and tide; Women's periodicals, English -- History -- 20th century; Women's periodicals, English -- Social aspects; Women's periodicals, English -- Political aspects; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Women's periodicals, English; Women's periodicals, English -- Social aspects; 1900-1999; Electronic books; History